A dust-enshrouded tidal disruption event with a resolved radio jet in a galaxy merger - S. Mattila; M. Pérez-Torres; A. Efstathiou; P. Mimica; M. Fraser; E. Kankare; A. Alberdi; M. Á. Aloy; T. Heikkilä; P. G. Jonker; P. Lundqvist; I. Martí-Vidal; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2022)
Tidal disruption events (TDEs) are transient flares produced when a star is ripped apart by the gravitational field of a supermassive black hole (SMBH). We have observed a transient source in the western nucleus of the merging galaxy pair Arp 299 that radiated > 1.5 x 10(52) erg at infrared and radio wavelengths but was not luminous at optical or x-ray wavelengths. We interpret this as a TDE with much of its emission reradiated at infrared wavelengths by dust. Efficient reprocessing by dense gas and dust may explain the difference between theoretical predictions and observed luminosities of TDEs. The radio observations resolve an expanding and decelerating jet, probing the jet formation and evolution around a SMBH.